Regional Parliaments and Democratic Crises: The Performance of ECOWAS and MERCOSUR Parliaments in the Democracy Protection Agenda. Issue 2 (26th November 2021) - Luciano, Bruno Theodoro; Ramanzini Júnior, Haroldo
Abstract: This article aims to examine regional parliaments of two prominent regional organisations in South America (Southern Common Market) and Western Africa (Economic Community of West African States), by focusing on their performance in the agenda of democracy protection. We comparatively assess the performance of regional parliamentary agents in contributing to the mediation and conflict resolution in cases of democratic breakdown as well as the conditions and factors that affect parliamentary performance. We argue that regional parliaments have exerted relevant agency in democratic crises, despite their low decision-making competencies and the strong intergovernmental features of Global South regional organisations.